Equity, social determinants and public health programmes - Blas, Erik (WHO GenevaCH, 2010)
Represents the major public health programmmes at WHO, reflecting the premise that health programmes must lead the way by demonstrating the relevance, feasibility and value of addressing social determinants. Takes a look at familiar problems which range from the overall structure of society, e.g. due to differences between segments of population or between societies, to differential exposure to risks and disparate vulnerability with populations, to individual differences in health care outcomes and their social and economic consequences. Identifies entry-points within existing health programmes, for interventions that address the causes of ill-health. Also identifies possible sources of resistance or opposition to change.